BODY MASS INDEX (BMI) SURVEY, BODY FAT PERCENTAGE, AND FOOD INTAKE OF THE BANYUMAS REGENCY WOMEN'S HANDBALL TEAM - Anisa Dwi Rahmawati; Siti Baitul Mukarromah (Riyadhoh : Jurnal Pendidikan Olahraga, 2026)
A high BMI can indicate a high level of body fatness. BMI filters out weight categories that may cause health problems, but does not diagnose body fatness or a person's health. In addition to BMI, fat control and healthy food intake also affect a person's health, including handball athletes in Banyumas Regency.The research method used is quantitative descriptive research through a direct survey approach. The research sample used was 14 handball athletes in Banyumas Regency using puposive sampling technique. The variables used are BMI, body fat percentage, and food intake.The results of this study are the average athlete has a normal Body Mass Index (21.32 kg/m2). The percentage of fat (57.14%) is more, energy consumption is 2136.56 calories, carbohydrates are 279.79 grams, protein is 83.76 grams, and fat is 75.95 grams.The conclusion of this research is the normal BMI and body fat percentage of handball athletes in Banyumas Regency with more categories, the test results of energy consumption levels are less, the level of energy adequacy is less, the percentage of carbohydrate intake is less, protein is more, and fat intake is more. Suggestions from researchers: pay attention to the intake of food consumed and maintain a diet, provide nutritious food, and work with sports sciece experts.